The Effect of Socialization of SAK EMKM, Accounting Understanding, and Level of Readiness of MSME Business Actors towards the Application of SAK EMKM in the Preparation of MSME Financial Reports (Case Study of MSMEs in Palembang City) - Yogi Darma Saputra; Leriza Desitama Anggraini; Muhammad Hamdan Sayadi (International Journal of Community Service & Engagement, 2022)
This study aims to analyze the influence of SAK EMKM socialization, accounting understanding, and the readiness of MSMEs actors to the application of SAK EMKM in preparing financial reports on MSMEs in Palembang city. The data used in this study were primary data obtained from questionnaires. The research method used is multiple linear regression analysis. The results prove that SAK EMKM (X1) has a negative effect on the application of SAK EMKM (Y). Meanwhile, understanding of accounting (X2) and the level of readiness of business actors (X3) have positive effect on the application of SAK EMKM (Y). This research is expected to help SMEs in preparing financial reports